Physico-chemical Studies, Thermal Decomposition Kinetics and Anti-fungal Studies of Some Bivalent Metal Complexes of Camphor-2-aminophenol - Marykutty, P.V.; Parameswaran, Geetha; S.S., Veena (Asian Journal of Chemistry, 2016)
The complexes of Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) with camphor-2-aminophenol (HCAP) have been synthesized and characterized on the basis of elemental analysis, molar conductance, magnetic moment, UV-visible and IR spectra. Co(II), Ni(II) and Mn(II) complexes of HCAP were subjected to thermal analysis so as to understand their thermal stability and decomposition patterns. The kinetic parameters like activation energy (E), frequency factor (A), entropy of activation (ΔS) and order parameter (n) were calculated from the TG curves, using Coats-Redfern equation. The ligand HCAP and its Co(II), Ni(II), Cu(II) and Zn(II) complexes were tested against the mycelial growth of Phytophthora capsici, a soil borne pathogen that affects and destroys black pepper.